2009
DOI: 10.1097/opx.0b013e3181bbca18
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Contact Lens Bacterial Contamination During Continuous Wear

Abstract: Purpose Microbial contamination of contact lenses is associated with corneal infection and inflammation. This study determined which microbiological, clinical and demographic factors are associated with bacterial contamination of a silicone hydrogel contact lens when worn for continuous wear. Methods Two hundred five normal subjects were enrolled in the Longitudinal Analysis of Silicone Hydrogel (LASH) Contact Lens Study and were fitted with lotrafilcon A lenses for monthly continuous wear and followed for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…The converse of this relationship is that limited bacterial diversity will be detected in non-disease continuous wear lenses, as was reported previously. 11 Based on our findings, and consistent with other biofilm infections, the severity of contact lens-related disease is predicted to increase with bacterial diversity. This notion is of clinical importance because infections caused by multiple bacterial species are problematic to treat.…”
Section: Discussionsupporting
confidence: 54%
“…The converse of this relationship is that limited bacterial diversity will be detected in non-disease continuous wear lenses, as was reported previously. 11 Based on our findings, and consistent with other biofilm infections, the severity of contact lens-related disease is predicted to increase with bacterial diversity. This notion is of clinical importance because infections caused by multiple bacterial species are problematic to treat.…”
Section: Discussionsupporting
confidence: 54%
“…22,54 As shown by other groups, significant levels of gram-negative bacteria were more common in subjects with active CIEs compared to healthy controls. 21,22,24,54 It is noteworthy that, while culturing is not the standard of care for CIEs considered to be low risk for MK, this study revealed that even mild to moderate case presentations harbored gram-negative bacteria known to be resistant to standard treatment regimens (e.g., Achromobacter xylosoxidans and Elizabethkingia and Delftia spp). 21,55 Consistent with previous findings, the bacteria identified on the majority of the healthy control subjects were normal commensal flora below our specified levels of substantial bioburden.…”
Section: Discussionmentioning
confidence: 98%
“…22 contact lens accessories samples were subjected to bacteriological analysis. Following bacterial isolates were isolated from the samples (Tables 1-4 Lens contamination is probably the greatest risk factor for corneal infection, the sources and factors leading to the contamination of microbes on lenses are of great interest [9]. Table 3: Isolation from contact lenses.…”
Section: Resultsmentioning
confidence: 99%
“…According to Loretta [9] the most likely route for contamination of contact lenses is from the skin to the lens. The evidence for this is that the majority of isolates found on contact lenses in their study were coagulase negative staphylococci which are normal, ubiquitous skin microbiota but in our study only 1 coagulase negative Staphylococci was isolated.…”
Section: Organismmentioning
confidence: 99%